The collective portrait of a municipal deputy of Perm region - Vitkovskaya, T.B. (Perm Federal Research Centre Journal, 2018)
The article attempts to construct "collective portraits" of municipal deputies, describing them as members of both professional and corporate groups, and determining how these characteristics affect their work as representatives of public authorities in municipalities. The typology of municipal deputies is presented (the criterion is the main sphere of their professional activity): "state employees", "businessmen", "factory workers" and "siloviki" ("security officials").